(untitled) (KULT_online, 2021)
Historians have studied for decades the commonality of Italian and German national histories in the nineteenth century. This edited volume aims instead to analyze them through gender and transnational lenses with a focus on women’s and Jewish history. What impact did the nationalist ideology have on the notion of womanhood, on female agency and Jewish identities, and how do family and religion relate to emancipation? These issues help reconsider the essentialism of national narratives and methodological nationalism in historical research.